A comparative study for the rate of adverse outcomes in unilateral and bilateral abdominal flap breast reconstruction: A meta-analysis. Issue 37 (11th September 2020) - Cao, Zheming; Cao, Jiri; Pang, Xiaoyang; Du, Wei; Wu, Panfeng
Abstract: Background: Adverse outcomes after unilateral vs bilateral breast reconstruction involve an unknown level of risk that warrants thorough investigation. Methods: To address this research need, PubMed, Ovid, Medline, EMBASE, and Scopus databases were searched through systematically from January 1, 1990, to January 1, 2019 to retrieve the relevant studies on the risk of postoperative complications after unilateral vs bilateral abdominal flap breast reconstruction. According to the pre-designed inclusion criteria, available data were extracted from the relevant studies, and then analyzed comparatively in order to identify the relative risk (RR) and 95% confidence intervals (CI) applying either a random or a fixed effects model. Results: Eventually, 20 studies involving 8122 female subjects met the inclusion criteria. It was found that unilateral reconstruction involved a significantly higher risk of flap loss (RR: 1.56, 95% CI: 1.21–2.00; P < .05) and fat necrosis (RR: 1.60, 95% CI: 1.23–2.09; P < .05) compared to bilateral reconstruction, while bilateral reconstruction involved a greater risk of abdominal hernia/bulge (RR: 1.67, 95% CI: 1.25–2.24; P < .05). The risk was found to be higher following bilateral free transverse rectus abdominis myocutaneous (fTRAM) flaps in comparison with deep inferior epigastric perforator (DIEP) flaps (RR: 2.62, 95% CI: 1.33–5.15; P < .05). Conclusion: The risk of postoperative flap complications in unilateral breast reconstruction is significantly higher than that in bilateral reconstruction. Contrarily, the abdominal complications were significantly higher in the bilateral group vs the unilateral group. Meanwhile, the risk of abdominal hernia/bulge complication after bilateral breast reconstruction was significantly higher with fTRAM vs DIEP. Therefore, DIEP flaps are recommended in priority for bilateral breast reconstruction, unless specifically contraindicated.